Кардиофункција, индикатори срчаног неуспешног рада и запаљни фактори код пацијената у току непрекидне лаге хипотермије хемодијализе након операције код болести клапана срца: Кардиофункција, индикатори срчаног неуспешног рада и запаљни фактори у непрекидној лаганој хипотермичној хемодијализи - Mao, Yun; Zhu, Li; Chen, Huilan; Li, Danxin; Yuan, Chikai; Wang, Renqiang; Liu, Jian (Journal of Medical Biochemistry, 2025)
Objective: To compare the effects of continuous hemodialysis at normal temperature and mild hypothermia in the treatment of cardiogenic shock after valvular heart disease surgery and its influences on patients’ cardiac function, heart failure indicators and inflammatory factors. Methods: After surgery for valvular heart disease, 180 patients with cardiogenic shock were brought to our hospital between January 2023 and December 2024. Patients in the control group received continuous hemodialysis treatment at normal temperature, whereas patients in the observation group received continuous hemodialysis treatment at mild hypothermia. The postoperative drainage volume, blood purification time, ventilator assistance time, ICU stay time, and occurrence of death, arrhythmia and infection were compared between the two groups. Cardiac function indicators, laboratory indicators of heart failure, serum creatinine (Cr), and inflammatory factor data were compared between the two patient groups prior to and following therapy. Results: Postoperative drainage volume, ventilator assistance time, intensive care unit (ICU) stay, blood purification time and mortality rate (P<0.05) were analyzed. The laboratory measurements of BNP, hs-CRP, and CR-related heart failure did not differ prior to treatment (P>0.05). BNP, hs-CRP, and CR-related heart failure were laboratory markers that were reduced in both groups after treatment; the levels in the observation group were lower than those in the control group (P<0.05). Tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1 (IL-1) were present at the same pretreatment levels in both groups (P>0.05). The levels decreased after treatment and were lower in the observation group than in the control group (P<0.05). Conclusion: For patients with cardiogenic shock after valvular heart disease surgery, mild hypothermia hemodialysis treatment can further reduce the postoperative drainage volume and hemopurification time, promote early recovery, and reduce the mortality rate. Moreover, mild hypothermia hemodialysis treatment can further improve the cardiac function of patients and alleviate heart failure. The levels of inflammatory factors in the patient’s body should be reduced.